Directional evidence conflict measurement approach - Lu WANG; Qing-hua XING; Yi-fan MAO (Tongxin xuebao)
Aiming at the problem that traditional evidence conflict measurement approaches can not express the differ-ence of mutual support degrees between evidences, a directional evidence conflict measurement approach was proposed. The conflict degree of evidences could be measured based on the new defined directional support degree, which imported the support coefficient to make the model dissymmetrical. Simulation results show that the proposed method can not only express the difference of mutual support degrees between evidences, but also solves the problem that traditional ap-proaches work poorly under special situation.